Agricultural Policies in Underdeveloped World Economies: A Study of Nigeria - Dance, Ayuba Maikasuwa; Choji , Felix Dalyop; Ibrahim, Muhammed Ohikwo (Kashere Journal of Politics and International Relations, 2025)
The primary challenge facing the underdeveloped world today is the pervasive menace of poverty. It stems from the apparent incapacity of certain Third World Countries to harness the agricultural resources bestowed by nature for the collective benefit of humanity. Conversely, post-colonial African countries, particularly Nigeria, have forsaken agricultural production over the past decade in favor of crude oil exploration, driven possibly by the allure of quick profits from oil sales. Consequently, many underdeveloped nations find themselves in significant socio-economic turmoil, exacerbated by the plummeting prices of crude oil in the international market. Beyond the economic downturn resulting from dwindling oil fortunes, leadership conflicts present another challenge. Policies are formulated without the necessary political will for execution, contributing to a general downward spiral of the system. This study reveals that the root cause of poverty in Africa, especially in Nigeria, lies in the mismanagement of the nation's political economy. The high expectations accompanying political independence have given way to escalating frustration, with the populace bearing the brunt of such misrule. The study serves as a theoretical exploration of poverty studies, relying on secondary materials for investigation. It emphasizes that overcoming these challenges, particularly in Nigeria, requires a renewed focus on agricultural production—a reliable strategy to effectively combat poverty and enhance overall agricultural productivity.